Semitic Dialects and Dialectology Fieldwork-Community-Change - Afkir, Mina (Heidelberg University Publishing (heiUP), 2022)
Characterised by the multiplicity and diversity of research and methodology, the European tradition of Semitic linguistics has always supported fieldwork and highly valued the data obtained in this way as it allows to create an interesting dynamic for linguistic studies itself. In the spirit of this tradition and to uphold it, the present book is a collection of articles based on data gathered primarily during field research expeditions. The volume is divided into two parts-Studies on various specific linguistic issues and Texts containing previously unpublished transcriptions of audio recordings in Arabic dialects, Maltese and Jibbali/Shehret.